Politician preferences and caps on political lobbying - Ivan Pastine; Tuvana Pastine (University College Dublin, UCD School of Economics, 2006)
This paper extends Che and Gale (1998) by allowing the incumbent politician to have a preference for the policy position of one of the lobbyists. The effect of a contribution cap is analyzed where two lobbyists contest for a political prize. The cap always helps the lobbyist whose policy position is preferred by the politician no matter whether it is the high-valuation or the low-valuation contestant. In contrast to Che and Gale, once the cap is binding a more restrictive cap always reduces expected aggregate contributions. However, the politician might support the legislation of a barely binding cap. When politician policy preferences perfectly reflect the will of the people, a more restrictive cap is always welfare increasing. When lobbyist's valuations completely internalize all social costs and benefits, a cap is welfare improving if and only if the politician favors the high-value policy. Even a barely binding cap can have significant welfare consequences.
hdl:10197/700
Keywords: D72; C72; 330; All-pay auction; campaign finance reform; explicit ceiling; Politiker; Interessenvertretung; Wahlkampffinanzierung; Wohlfahrtsanalyse; Spieltheorie; Politisches Ziel